Digital Media Utilization in Enhancing Political Participation Among Young Voters in the General Election - Dita Febryanti; Syan Adiwinata (Talenta Publisher, 2026)
Elections are a crucial moment in any democracy, yet first-time voter turnout tends to be low. This study explores the role of the digital platform Bijakmemilih.id in increasing the participation of first-time voters in the 2024 Indonesian elections. It focuses on analyzing the platform's contribution to encouraging political engagement among this voter group. The objectives of this study are to identify the platform’s impact on first-time voter engagement, examine the factors influencing increased participation, and evaluate the extent to which the platform can be effectively adopted by first-time voters. This research employs surveys and literature review to identify the research problem and applies a mixed-methods approach to answer the research questions. The findings indicate that Bijakmemilih.id plays a significant role in enhancing the participation of first-time voters in the 2024 elections. The platform effectively promotes both electoral participation and broader political involvement, such as engagement in social movements. Key factors supporting its effectiveness include contextual information delivery, voter-centered orientation, continuous information flow, content segmentation tailored to young voters, and opportunities for active participation. Although the platform shows a high adoption rate, further improvement in political literacy and the development of a volunteer spirit are needed to ensure its sustainable use in the future.